TOXIC EFFECT OF DIFETHIALONE ON THE LIVER OF SWISS ALBINO MICE, MUS MUSCULUS - SAHNI, KAVITA; SAXENA, Y. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Studies were carried out on the hepatic alterations induced due to difethialone (LM-2219). [3-4-bromo (1,1'- biphenyl-4-yl) -1, 2, 3, 4 - tetrahydro - 1 - naphthalley] -4-hydroxy treatment in Swiss albino mice. Difethialone is the newly developed anticoagulant rodenticide causing severe and irreversible hepatic damage even in lower doses. The changes were visible after one day of the poison feeding but these were more severe at later stages. Higher dosages of difethialone showed more pronounced pathological lesions at early autopsy intervals. The changes included migration of nuclei, dilation of sinusoids, swelling of hepatocytes, fatty degeneration with vacuolization, lymphocytic infiltration in and around portal and central veins and in sinusoids. Mild to moderate fibrosis, hyperplasia cytoplasmolysis and karyolysis were also observed at various stages and intervals of different doses of the anticoagulant. Complete deformity of cellular architecture of liver was observed in later autopsy intervals.